2023
DOI: 10.3390/cells12020275
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Mitochondrial Function in Hutchinson-Gilford Progeria Syndrome by the Pharmacological Modulation of Exportin CRM1

Abstract: Hutchinson-Gilford progeria syndrome (HGPS) is a rare premature aging disorder caused by the expression of progerin, a mutant variant of Lamin A. Recently, HGPS studies have gained relevance because unraveling its underlying mechanism would help to understand physiological aging. We previously reported that the CRM1-mediated nuclear protein export pathway is exacerbated in HGPS cells, provoking the mislocalization of numerous protein targets of CRM1. We showed that normalization of this mechanism by pharmacolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…and respiratory capacity, high ROS levels and low PGC1a levels also accumulated in Progeria. 44,45 Recently, null mutations in Metaxin-2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and respiratory capacity, high ROS levels and low PGC1a levels also accumulated in Progeria. 44,45 Recently, null mutations in Metaxin-2…”
Section: Discussionmentioning
confidence: 99%
“…Typical “Progeria” disease known as Hutchinson‐Gilford syndrome (HGPA) occurs due to single gene mutation in nuclear gene Lamin A causing aberrant nuclear structure and cell division. Moreover, dysfunctional mitochondria with fragmented morphology, low membrane potential and respiratory capacity, high ROS levels and low PGC1a levels also accumulated in Progeria 44,45 . Recently, null mutations in Metaxin‐2 were found in progeroid disorder mandibuloacral dysplasia 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this signalling cascade provides key mechanic insights that relate to NAD+ depletion known to play a fundamental role in the biology of aging ( Verdin, 2015 ). In HGPS, autophagy ( Marino et al, 2008 ), UPR ( Vidak et al, 2023 ) and mitophagy ( Monterrubio-Ledezma et al, 2023 ) are apparently not compromised but even increased likely in an attempt to compensate for massive progerin accumulation. Consistent with this notion Vidak and colleagues have shown that in HGPS UPR machinery of the endoplasmic reticulum senses nucleoplasmic progerin aggregates through clustered Sun proteins a mechanism that awaits to be tested in physiological age-related conditions ( Vidak et al, 2023 ).…”
Section: Hallmarks Of Aging In the Context Of Progeroid Syndromesmentioning
confidence: 99%
“…HGPS cells exhibited enhanced nuclear protein export activity due to the progerin-driven overexpression of chromosomal region maintenance 1 (CRM1). Pharmacologically inhibiting CRM1 with Leptomycin B mitigates the senescent phenotype of HGPS cells [ 119 ]. High levels of interleukin-6 (IL-6), a pro-inflammatory cytokine associated with age-related processes, have been observed in HGPS cells and mouse models ( Lmna G609G/G609G ).…”
Section: Treatments and Clinical Trials For Hgpsmentioning
confidence: 99%